Performing Historical Monarchs in Early Modern England: Beyond the History Play - Kit Heyam (Royal Studies Journal, 2021)
This article discusses the use of performative techniques in prose accounts of the past written in early modern England. Building on scholarship that has located the source of early modern emotional engagement with the past in the history play, it shows that prose texts should be seen alongside history plays as forms that provided access to performance of historical characters. Chronicles, political texts, and other prose accounts of the past deployed invented speech, performative description, and interiorised characterisation at moments of heightened emotional and political intensity. Focusing as a case study on accounts of the reign of Edward II—which attracted substantial cross-genre attention, particularly from the second half of the sixteenth century onwards, owing to its paradigmatic status as an exemplum of overmighty favourites and deposition, and which was shaped by writers of all genres into an emotionally compelling de casibus narrative structure—this article shows that the use of performative techniques in these texts facilitated both emotional and political engagement with the past. Attention to these performative elements of historical prose thus prompts us to reassess the complexity, interiority and vividness of chronicles; to reimagine the place of history plays in early modern culture, as one among many forms which provided access to performance of historical characters; and to augment our understanding of the process by which history was made usable; to reconfigure our understanding of the nature of early modern people’s relationship to the past, underlining the significance of the emotional dimension of that relationship alongside the utilitarian.